In-situ extraction by solid-phase micro-extraction and comparison of volatile compounds in mango cultivars (Mangifera indica L.) resistant and susceptible to the fruit fly Anastrepha obliqua Macquart (Diptera: Tephritidae) - Tosta, C. D. [UNESP]; Silva, A. A. [UNESP]; Pinto, M. C. [UNESP]; Machado, V. E. [UNESP]; Cavalheiro, A. J. [UNESP] (International Society for Horticultural Science (ISHS), 2017)
Many commercial cultivars of mango (Mangifera indica L.) are susceptible to fruit fly pests, such as Anastrepha obliqua, so growers use chemical pesticides, burdening production and generating environmental problems. Some mango cultivars are resistant to fruit flies and therefore have factors that differentiate them compared with susceptible cultivars. The objective of this study was to explore compounds and to identify factors of resistance and/or attraction. Resistant and susceptible fruit volatile compounds obtained by in-situ solid-phase micro-extraction (SPME) were identified and compared. Electroantennographic and wind tunnel attraction tests were performed using the proportion of major compounds emitted by mango fruits. Green fruits showed no esters, which became part of the main compounds in the mature stage, mainly ethyl octanoate and methyl octanoate. The compounds found in greater quantities in resistant cultivars were limonene, myrcene and humulene, while those that marked the condition of susceptibility were ethyl octanoate, methyl octanoate, δ-3-carene and allo-aromadendrene. A synthetic blend based on nine main compounds of cultivar 'Palmer' proved attractive to Anastrepha obliqua in the wind tunnel.
Keywords: Anastrepha obliqua; Fruit flies; Mangifera indica; Mango; Volatile compounds